1986
DOI: 10.1080/00039896.1986.9938335
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Indicators of Inorganic Mercury Toxicity

Abstract: Forty-two workers from a chemical plant producing inorganic mercury compounds were evaluated for neurologic, nephrotic, and ophthalmologic toxicity. Despite elevated blood and urinary mercury levels, routine clinical testing such as physical examination, blood chemistries, and urinalysis were generally normal. These findings from the routine examination are in contrast to the complaints of neuropsychological symptoms, elevated urinary n-acetyl B-D-glucosaminidase (NAG) levels, decreased motor nerve conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…and enzymuria (û-galactosidase, N-acetyl-û-D-glucosaminidase (NAG), û-glucuronidase, etc.) [4,6,11,13,22,28,31,32,34]. These manifestations can diminish the ability of proximal tubule segments to reabsorb water, proteins, and other substances, thus aecting the kidneys' ability to maintain volume and composition of body¯uids within normal limits.…”
Section: Introductionmentioning
confidence: 96%
“…and enzymuria (û-galactosidase, N-acetyl-û-D-glucosaminidase (NAG), û-glucuronidase, etc.) [4,6,11,13,22,28,31,32,34]. These manifestations can diminish the ability of proximal tubule segments to reabsorb water, proteins, and other substances, thus aecting the kidneys' ability to maintain volume and composition of body¯uids within normal limits.…”
Section: Introductionmentioning
confidence: 96%
“…The blood mercury level is the best measure of recent exposure but has no good correlations with the clinical features in chronic intoxication. On the contrary, Rosenman et al [1986] reported that neuropsychological symptoms and other toxic manifestations had good correlations with urinary mercury levels or 24-hr urinary mercury outputs. We could not find significant correlations between EP abnormalities and body mercury levels in the present study, but these EP changes were mainly seen in mercury workers with high exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Relationships between mercury levels and clinical manifestations have been extensively investigated in mercury exposure or intoxication [Rosenman et al, 1986;Ellenhorn and Barceloux, 19881. The blood mercury level is the best measure of recent exposure but has no good correlations with the clinical features in chronic intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…Rosemann et al [26] found positive correlation between HgU levels (100 µg -250 µg/L) and neuropsychological symptoms. In a study conducted by Smith et al, [27] short-term memory was affected in a group of individuals with a mean of 180 µg/ L.…”
Section: Discussionmentioning
confidence: 99%